Hox gene expression in larval development of the polychaetes Nereis virens and Platynereis dumerilii (Annelida, Lophotrochozoa) - Kulakova, Milana A.; Arendt, Detlev (Development genes and evolution, 2007)
The bilaterian animals are divided into three great branches: the Deuterostomia, Ecdysozoa, and Lophotrochozoa. The evolution of developmental mechanisms is less studied in the Lophotrochozoa than in the other two clades. We have studied the expression of Hox genes during larval development of two lophotrochozoans, the polychaete annelids Nereis virens and Platynereis dumerilii. As reported previously, the Hox cluster of N. virens consists of at least 11 genes (de Rosa R, Grenier JK, Andreeva T, Cook CE, Adoutte A, Akam M, Carroll SB, Balavoine G, Nature, 399:772-776, 1999; Andreeva TF, Cook C, Korchagina NM, Akam M, Dondua AK, Ontogenez 32:225-233, 2001); we have also cloned nine Hox genes of P. dumerilii. Hox genes are mainly expressed in the descendants of the 2d blastomere, which form the integument of segments, ventral neural ganglia, pre-pygidial growth zone, and the pygidial lobe. Patterns of expression are similar for orthologous genes of both nereids. In Nereis, Hox2, and Hox3 are activated before the blastopore closure, while Hox1 and Hox4 are activated just after this. Hox5 and Post2 are first active during the metatrochophore stage, and Hox7, Lox4, and Lox2 at the late nectochaete stage only. During larval stages, Hox genes are expressed in staggered domains in the developing segments and pygidial lobe. The pattern of expression of Hox cluster genes suggests their involvement in the vectorial regionalization of the larval body along the antero-posterior axis. Hox gene expression in nereids conforms to the canonical patterns postulated for the two other evolutionary branches of the Bilateria, the Ecdysozoa and the Deuterostomia, thus supporting the evolutionary conservatism of the function of Hox genes in development.